2017
DOI: 10.1080/09638288.2017.1289418
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal complaints in individuals with finger or partial hand amputations in the Netherlands: a cross-sectional study

Abstract: Purpose: To compare the prevalence of musculoskeletal complaints (MSCs) in individuals with finger or partial hand amputations (FPHAs) with a control group and to explore the effect and predictors of MSCs in individuals with FPHAs. Method: A questionnaire-based cross-sectional study was conducted. The primary outcome measures were: prevalence of MSCs, health status, pain-related disability, physical work demands, work productivity, and hand function. Results: The response rate was 61%. A comparable proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…It is also possible that those with shorter residual limbs have a greater reliance on the nonamputated limb for activity performance, given that items on the AM-ULA are scored lower if the prosthesis is used passively or not at all. 27 Although not statistically significant across all domains, our study indicates that shoulder pain in the moderate intensity range is associated with functional performance and HRQOL outcomes in long-term upper limb prosthesis users. Our study specifically found a negative correlation coefficient between contralateral shoulder pain and measures of upper limb disability and the physical component of HRQOL.…”
Section: Discussioncontrasting
confidence: 55%
“…It is also possible that those with shorter residual limbs have a greater reliance on the nonamputated limb for activity performance, given that items on the AM-ULA are scored lower if the prosthesis is used passively or not at all. 27 Although not statistically significant across all domains, our study indicates that shoulder pain in the moderate intensity range is associated with functional performance and HRQOL outcomes in long-term upper limb prosthesis users. Our study specifically found a negative correlation coefficient between contralateral shoulder pain and measures of upper limb disability and the physical component of HRQOL.…”
Section: Discussioncontrasting
confidence: 55%
“…Probabilities of these complications are given in Table 1. 4,5,7,8,9,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33…”
Section: Methodsmentioning
confidence: 99%
“…Although these studies contribute largely to our knowledge about perceived function and other factors, most are limited to the veteran population, do not model the impact that both satisfaction and pain could have on perceived function, and/or do not use a PRO that solely focuses on perceived function. Many studies examining the upper limb prosthesis user population also fail to include partial hand/finger amputation levels 10,13‐15 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies examining the upper limb prosthesis user population also fail to include partial hand/finger amputation levels. 10,[13][14][15] Understanding the gaps identified from recent literature, the goal of this study was to use the ICF model to identify which health condition-related, body function, environmental, and personal factors influence activity as measured by perceived function in the upper limb prosthesis user population, with a focus on the U.S. civilian population and inclusion of individuals with distal limb loss/difference. Having a clear understanding of the factors that influence perceived function can help improve the overall rehabilitation approaches for this unique patient population.…”
Section: Introductionmentioning
confidence: 99%